Flood Risk Mapping Using Ahp Method A Case Study For Meru, Klang - Isman, Intan Shafinaz (Universiti Sains Malaysia, 2022)
Malaysia is typically accompanied by annual flooding caused by the seasonal monsoon, resulting in significant losses. Flood risk, exposure, and flood damage are rising, increasing poverty and vulnerability. The annual occurrence of the flood hazard has compelled residents to plan ahead of time in order to return to their normal lives as quickly as possible. This study focused on the flood event in Meru that occur during December 2021, where the road on Meru has become inundated as a result of around 15 hours of nonstop rainfall, leading many areas of Klang to become inundated with waist-high water. Flood risk is developed at the regional and administrative levels using a multi-criteria decision-making analysis (MCDM) - analytical hierarchy process (AHP). The criteria characterize the relevant considerations of Meru, Klang, including slope, elevation, and aspect, buffer from river, road, and forest, and type of land use. This study aimed to determine the criteria of flood risk in Meru, Klang, Selangor and to analyze of MCDM-AHP based on critical criteria determined from literature. Standardization, expert work, weighting, summary analysis, aggregation, and validation of all decision-making criteria to be considered are all part of this phase. Residential and industrial land uses, buffers from roads, and buffers from rivers all played a significant role in flood incidence in the study area, with selected factor weight values of 0.367, 0.090, and 0.081, respectively. The current study's findings will support planners in developing flood mitigation strategies and will serve as a foundation for future research in the study area as part of flood preparedness.